2015 8th International Conference on Intelligent Computation Technology and Automation (ICICTA) 2015
DOI: 10.1109/icicta.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Evaluation of the Chinese IP Geolocation Databases

Abstract: Direct query to IP geolocation databases is a convenient and widespread way for determining geographic location where a host with corresponding IP address is. However, many databases available on the Internet may not provide accuracy data as they claim. In this paper, we focus on analyzing IP addresses of mainland China recorded in popular China-based IP geolocation databases. First, distributions and characteristics of IP addresses and blocks of mainland China at different geographic granularities are analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, IP geolocation databases provide city-level granular IP location information. Studies have shown that this information is highly credible at the national and provincial levels and lower at the city level [18,19]. Although the credibility of the city information of an IP address provided by IP geolocation databases is not high, the information can still be used to infer the reliability of a candidate landmark.…”
Section: One Domain Name Mapping To One Ip Addressmentioning
confidence: 99%
“…Moreover, IP geolocation databases provide city-level granular IP location information. Studies have shown that this information is highly credible at the national and provincial levels and lower at the city level [18,19]. Although the credibility of the city information of an IP address provided by IP geolocation databases is not high, the information can still be used to infer the reliability of a candidate landmark.…”
Section: One Domain Name Mapping To One Ip Addressmentioning
confidence: 99%
“…Using databases' API interface can get a lot of landmarks in a short time. But, the accuracy of the landmarks provided by these databases is only at the city level, and the overall reliability of the database is not high enough [Shavitt and Zilberman (2011); Backstrom, Sun and Marlow (2010); Poese, Uhlig, Kaafar et al (2011); Li, Zhang, Wang et al (2017); Li, He, Xi et al (2015)]. Therefore, it is hard to obtain a large number of reliable street-level landmarks using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Poese et al [19] studied IP location databases such as MaxMind, IP2LOCATION, IPInfoDB, and HostIP, found that the vast majority of IP data in United States were inconsistent with IP initial allocation data, and pointed that the city-level location of IP in these databases was inaccurate. In [20,21], the authors analysed the distribution characteristics of IP address blocks of different geographic granularity in mainland China, compared the data consistency between multiple IP location database, verified the accuracy of the IP location database using a small number of existing landmarks, and improved the accuracy of the database by clustering IP blocks at different locations. For improving the accuracy of database, location data collected from search engine logs [22], IP allocation strategy of ISPs, urban areas, and population [23] were introduced into the database evaluation methods.…”
Section: Introductionmentioning
confidence: 99%